Focused operations management : achieving more with existing resources - Ronen, Boʻaz (Wiley, 2008)
"With its focus on increasing throughput, reducing response time, and creating value, Focused Operations Management gives you the knowledge and methodology to turn around any organization in almost any industry. Completely up to date and packed with expert insight and real-life examples, this thorough guide is the ultimate resource for any business struggling to succeed in the hyper-competitive global marketplace."--Jacket